2012
DOI: 10.1063/1.4770359
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Ge2Sb2Te5 films by amplified femtosecond optical pulses

Abstract: The phase transition between the amorphous and crystalline states of Ge 2 Sb 2 Te 5 has been studied by exposure of thin films to series of 60 femtosecond (fs) amplified laser pulses. The analysis of microscope images of marks of tens of microns in size provide an opportunity to examine the effect of a continuous range of optical fluence. For a fixed number of pulses, the dependence of the area of the crystalline mark upon the fluence is well described by simple algebraic results that provide strong evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…Recent studies demonstrated the cumulative switching of GST films induced by ultrafast lasers [3,5,6]. The repeatable energy dose and rapid heat diffusion allow continuous change of its optical reflectivity, which can be used to emulate biologically inspired synaptic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated the cumulative switching of GST films induced by ultrafast lasers [3,5,6]. The repeatable energy dose and rapid heat diffusion allow continuous change of its optical reflectivity, which can be used to emulate biologically inspired synaptic functions.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that crystallization of a-GST by fs pulses 26 is very sensitive to the details of the sample stack. The presence of a capping layer or underlayer or a difference in sample thickness, can significantly modify heat flow within the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The chalcogenide alloy such as Ge 2 Sb 2 Te 5 (GST), has been extensively adopted for phasechange probe memory applications owing to its relative easiness for phase transformation, good stability and large reading contrast. [21][22][23][24] Consequently, the integration of the superb characteristics of GST alloy as recording media together with the use of nanoscale conductive probe for recording equipment renders phase-change probe memory advantageous as a \universal" memory over other storage forms. First, it may be possible to use phasechange probe memory as cache memories.…”
Section: Introductionmentioning
confidence: 99%